The really, really, really easy step-by-step guide to build your own website - Hoole, Gavin; Smith, Cheryl (London : New Holland, 2008)
This step-by-step guide to building your own website shows you how to create a stunning site, register your domain, publish your site and attract search engine traffic.
"For absolute beginners of all ages."--Cover.
Includes index.
Keywords: Internet; WebSite (Computer file).; World Wide Web